Keripik Rambutan Arialaka (Naphelium Lappaceum L): Karakteristik Sensori dan Fisikokimia Dengan Metode Vaccuum Frying - Noviandia, Halpi; Hutami, Rosy; Sunarmani, Sunarmani (Jurnal Ilmiah Pangan Halal, 2022)
Rambutan chips are dry food made from rambutan fruit, this healthy snack contains fiber and the benefits of being cooked using a vacuum frying machine. This study aims to determine the effect of adding citric acid and sodium metabisulfite and the effect of the blanching process on rambutan chips. Completely Randomized Design (CRD) 2 factors used in this study. The analysis carried out was total dissolved solids, glucose content, total acid, vitamin C content, acidity degree (pH), crude fiber content, chemical tests (moisture content, ash content, protein content, fat content, carbohydrate content), physical tests (test ), texture and color test), and sensory test (hedonic). Data analysis used ANOVA and Duncan’s advanced test. The selected rambutan chips are A2B2 (Na2S2O5 0.2% and Non-Blanching) with a reddish yellow physical color, crunchy physical (hardness), and a carbohydrate content of 49.11%, fat content of 38.74%, total dissolved solids of 24.50 degree Brix, reducing sugar content 16.60%, protein content 8.12%, pH 4.84, moisture content 3.61%, crude fiber content 3.35%, total acid content 0.73%, ash content 0.39 %, and levels of vitamin C 250.24 mg/100 g.